Fejezetek, arcképvázlatok a DEAC labdarúgó szakosztályának történetéből - Gápel, Endre (Gerundium, 2018)
Chapters and Sketches of Portraits pertaining to the History of the Soccer Division of the Debrecen University Athletic Club. The Athletic Club of the University of Debrecen (DEAC) was established on the first day of August, 1919, by the University’s managers, professors and various renowned public figures with the primary objective of ensuring sporting opportunities and facilities for the student body, the educators and other employees of the University. The soccer club of DEAC achieved the peak of its development in the 1960s and 1970s, when the University’s team managed to qualify to play in the second division of the national football league (NB II). In those days the team attracted large crowds. Each team member was a student and they also were successful as students. Besides offering a survey of tangible successes in football, the present discussion also highlights the subsequent careers of the respective members of the team. A number of these successful soccer players also achieved outstanding professional careers, some of them became professors, well-known medical doctors, school pricipals, and sports managers of international rank The survey also introduces those university managers who supported and promoted the quality sporting activities of the students. The essay is a much-needed elaboration adding substantially to a better understanding of the scope, the past and present of the University of Debrecen. It is both a history of sport and the history of an institution.